Lumen-apposing metal stent through the meshes of duodenal metal stents for palliation of malignant jaundice - Mangiavillano, Benedetto; Kunda, Rastislav; Robles-Medranda, Carlos; Oleas, Roberto; Anderloni, Andrea; Sportes, Adrien; Fabbri, Carlo; Binda, Cecilia; Auriemma, Francesco; Eusebi, Leonardo H.; Frazzoni, Leonardo; Fuccio, Lorenzo; Colombo, Matteo; Fugazza, Alessandro; Bianchetti, Mario; Repici, Alessandro (Endoscopy International Open, 2021)
Background and study aims Endoscopic retrograde cholangiopancreatography (ERCP) is the gold standard procedure for malignant jaundice palliation; however, it can be challenging when a duodenal self-expandable metal stent (SEMS) is already in place.Patients and methods The primary aim of our study was to evaluate the technical feasibility of the placement of a lumen apposing metal stent (LAMS) through the mesh (TTM) of duodenal stents. The secondary aims were to evaluate clinical outcomes and adverse events (AEs) related to the procedures.Results Data from 23 patients (11 F and 12 M; mean age: 69.5 ± 11 years old) were collected. In 17 patients (73.9 %) TTM LAMS placement was performed as first intention, while in six patients (26.1 %) it was performed after a failed ERCP. Thirteen patients (56.5 %) underwent the procedure due to advanced pancreatic head neoplasia. One technical failure was experienced (4.3 %). The TTM LAMS placement led to a significant decrease in the serum levels of bilirubin, ALP, GGT, WBC and CRP. No cases of duodenal SEMS occlusion occurred and no other AEs were observed during the follow-up.Conclusions Concomitant malignant duodenal and biliary obstruction is a challenging condition. Palliation of jaundice using TTM LAMS in patients already treated with duodenal stent is associated to promising technical and clinical outcomes.